Metachronous occurrence of two different histological subtypes of endometriosis-related neoplasms - Takashi Uehara; Hiroshi Yoshida; Keisei Tate; Tomoyasu Kato (Elsevier, 2019)
A solitary pelvic tumor after treating a primary endometriosis-related neoplasm is usually considered a recurrence but may actually be a primary endometriosis-related peritoneal neoplasm. A Japanese woman in her late 60s was referred to our hospital for a solitary pelvic tumor. The tumor was suspected as a recurrence of a previously treated stage IA ovarian clear-cell carcinoma, and resected. Pathological analysis revealed that the tumor was a peritoneal seromucinous carcinoma associated with pelvic endometriosis. Both tumors displayed distinct histopathologies, although both neoplasms were endometriosis related. An apparent recurrent tumor after treating of an endometriosis-related neoplasm might not be a true recurrent tumor but a second primary endometriosis-related neoplasm. Histological confirmation is indicated in such cases. Keywords: Clear cell carcinoma, Endometriosis, Endometriosis-related neoplasm, Ovarian cancer, Seromucinous carcinoma